User-centered design by genetic algorithms: Application to brass musical instrument optimization - Poirson, Emilie; Dépincé, Philippe; Petiot, Jean-François (Engineering applications of artificial intelligence, 2007)
This work presents an implementation of genetic algorithms (GAs) for a user-centered design of products. It describes at first a methodology for a user-centered design, based on the coupling between a subjective study to define desirable features and on objective study to find out the influencing objective variables. It relies on two domains that remain generally distinct: the design with a scientific approach (generally math-based) and the design with a sensory and perceptual approach (subjective). The methodology is presented on a particular product for which the perceived aspects are essential: a musical instrument (trumpet). Two types of study were carried out on a set of trumpets: firstly, a sensory study, which aim is to characterize the perception of the intonation of the instruments by musicians; secondly, an objective study, which consists in an objective description of the instruments by physical measurements (impedance). We correlated the intonation assessments data and the physical measurements, in order to deduct useful objective functions for the design of a new instrument, and to formulate the user-centered design problem as a multi-objective optimization problem. The paper presents next how GAs were implemented to solve the multi-objective optimization problem.